Piecewise empirical model for shielding effectiveness prediction of graphite-cement powder mixture - See, Khee Yee (2014)

(untitled)
The addition of conductive fillers into insulating matrix will improve its shielding effectiveness (SE). In this work, the graphite fine powder is added into the cement powder for SE enhancement. The SE of the mixture can be calculated analytically but this requires dielectric properties of the mixture. When there are changes of mixture proportion, a new dielectric measurement must be repeated. This is inconvenient especially to the civil engineers who are more concern on the relationship between the percentages of additive to the resultant SE. A piecewise empirical model which is working in between 100 MHz to 2000 MHz is proposed in this work. The model able to estimate the SE of the graphite-cement mixture with thickness of 1 cm. Different graphite-cement samples with different percentage of graphite fine powder are prepared and dielectric measurements are executed to obtain their dielectric properties. Their SE are analytical calculated based on the measured properties and it is used to establish the model for SE prediction. Based on this model the users able to predict the resultant SE of the mixture and hence proposed the best graphite-cement proportion to fulfill the cost effective requirement